Electronic Goods/Services Procurement Policy Implementation at the Ministry of Energy and Mineral Resources - Nova Magdalena Ginting; Herijanto Bekti; Sawitri Budi Utami (Jurnal Manajemen Pelayanan Publik, 2023)
The government institution responsible for managing energy and mineral resources in Indonesia is the Ministry of Energy and Mineral Resources (MEMR). In carrying out its responsibilities, the MEMR procures goods/services to support its operational activities. To ensure transparency, accountability, and effectiveness in using the state budget, crucial to research the effective implementation of electronic procurement of goods and services in the MEMR. This research examines how the MEMR has implemented electronic procurement of goods and services. Based on the literature review, similar research has yet to be conducted. The research methodology used is qualitative descriptive. The findings of this study demonstrate that the MEMR's e-procurement policy has been successfully implemented. However, several things become input from researchers, namely that the MEMR is serious about improving the standards and maturity of e-procurement services; improving a professional work culture with integrity and optimizing the use of information technology in e-procurement; increasing communication with Government Goods/Services Policy Agency, and in order to have good legal standing in strengthening the procurement of goods and services in Indonesia, it is necessary to encourage the creation of a legal basis for goods and services procurement regulations in the form of laws.